Dispersion of refractive index in thin films CdI2 and ZnI2 - Yunakova, O.N.; Miloslavsky, V.K.; Kovalenko, E.N. (Institute for Single Crystals, 2010)
The refractive index dispersion in thin CdI2 and ZnI2 films has been measured in the wavelength interval 300-1000 nm and processed using the monooscillator model ageeing well with experimental data. The optical permittivity e_unlim of both compounds has been determined using the found parameters of this model, the optical permittivity data have been used in the further analysis of exciton states in CdI2 and ZnI2, in particular, for determination of 1s exciton radius. The found a_ex values are close to the unit cell parameters of the compounds, thus indicating that the excitons in two compounds belong to excitons of the intermediate electron-hole band.
Keywords: оптика; кафедра физической оптики; CdI2; ZnI2; показатель преломления; модель Вемпла; эффективная диэлектрическая проницаемость; экситон